AUTHENTHIC PROBLEM BASED LEARNING (aPBL) UNTUK MENINGKATKAN KEMAMPUAN BERPIKIR SISWA - Hudha, Muhammad Nur (Jurnal Pendidikan Matematika dan IPA, 2017)
The purpose of physics learning at the school level is directed to develop the students’ thinking skill. This study aimed to improve the students’ critical thinking skill and students’ problem solving skill through aPBL (authenthic Problem Based Learning) learning. This study used classroom action research designed by Kemmis & Mc Taggart with the stages; problem identification, action planning, action, observation, and reflection. The research data were obtained in the form of the data of students’ problem-solving skill and critical thinking. The data in this research were analyzed qualitatively and quantitatively. The results showed that the application of aPBL (authentic Problem Based Learning) could  improve the students' critical thinking skill and  students’ problem solving skill. This improvement could be seen from the average score of critical thinking test and problem solving skill test that had been carried out. Keywords: aPBL, thinking skill, physics